A CLINICAL CASE OF LYSIS OF THROMBUS IN THE LEFT ATRIAL APPENDAGE IN A PATIENT WITH ATRIAL FIBRILLATION PREVIOUSLY TREATED WITH WARFARIN - T. A. Barbashina; O. Yu. Makhova («REMEDIUM GROUP» Ltd., 2020)
The article describes the clinical observation of LAA thrombosis in a 46-year-old patient with atrial fibrillation that first occurred during taking warfarin; discusses further management of the patient. Due to inefficacy of medical cardioversion (CV) and the need to restore sinus rhythm, electric CV was planned. Before the planned restoration of the rhythm, transesophageal echocardiography was performed and a thrombus in the LAA was detected. Given that the patient had been on adequate warfarin therapy for a long time, it was decided to prescribe a drug from the direct oral anticoagulants group dabigatran etexilate at a dose of 150 mg BID for 8 weeks. The control transesophageal echocardiographic examination showed evidence of complete lysis of thrombus.